2017
DOI: 10.1002/2016jd026251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthropogenic activity emerging as intensified extreme precipitation over China

Abstract: This study aims to provide an assessment of the effects of anthropogenic (ANT) forcings and other external factors on observed increases in extreme precipitation over China from 1961 to 2005. Extreme precipitation is represented by the annual maximum 1 day precipitation (RX1D) and the annual maximum 5 day consecutive precipitation (RX5D), and these variables are investigated using observations and simulations from the Coupled Model Intercomparison Project phase 5. The analyses mainly focus on the probability‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 62 publications
6
47
0
Order By: Relevance
“…The increase is mainly located in South China, whereas the decrease in North China. This structure is consistent with the change in mean precipitation observed in China during this period, which is known as the flooding in the south and drought in the north pattern, and is in visual agreement with the study reported by H. X. Li, Chen, et al (). However, the number of stations with significant trends is relatively small: 4% show a significant increasing trend of extreme precipitation and only 0.66% show a significant decreasing trend, with both trends randomly distributed across the region.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The increase is mainly located in South China, whereas the decrease in North China. This structure is consistent with the change in mean precipitation observed in China during this period, which is known as the flooding in the south and drought in the north pattern, and is in visual agreement with the study reported by H. X. Li, Chen, et al (). However, the number of stations with significant trends is relatively small: 4% show a significant increasing trend of extreme precipitation and only 0.66% show a significant decreasing trend, with both trends randomly distributed across the region.…”
Section: Resultssupporting
confidence: 93%
“…They concluded that a response to anthropogenic forcing emerges for all models by 2040. However, H. X. Li, Chen, et al () found an increase in extreme precipitation events over China in recent decades and detected an anthropogenic influence in these events. The discrepancy between these results and our findings may be due to a number of factors, but the use of different data sets may be the main cause.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, China has experienced an increase in extreme climate events, some of which present widespread impacts, including deaths, severe ecosystem damage, and large economic losses. These increased extreme events in China have had detectable anthropogenic influences with a high confidence level for temperature‐related extremes but a low confidence level for precipitation‐related extremes (Sun et al, ; Chen and Sun, , , ; Li et al, ; Ma et al, ). Here, we present an analysis of a set of extreme climate events in China, including the wide‐ranging cold event across China in January 2011, extreme hot event over eastern China from July to August 2013, large‐scale heavy rainfall over northern China in July 2012, and severe drought over NC from July to August 2014.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the influences of external forcings on the variations of SHDEs over NEC, multi‐model simulations from different external forcings during the period from 1961 to 2005 are used, including historical anthropogenic plus natural forcing (ALL), natural forcing (NAT), and greenhouse gases forcing (GHG). In this study, the anthropogenic impact (ANT) is calculated as ALL minus NAT (Zhang et al, ) and that the other anthropogenic forcing (OA) such as aerosol emissions and land use can be obtained as ANT minus GHG (Li et al, ). For the purpose of detection and attribution analyses, the preindustrial unforced control (CTL) simulations are also selected.…”
Section: Methodsmentioning
confidence: 99%